KARAKTERISTIK BATUAN BEKU ANDESIT & BREKSI VULKANIK, DAN KEMUNGKINAN PENGGUNAAN SEBAGAI BAHAN BANGUNAN DAERAH UKIR SARI, KECAMATAN BOJONEGARA KABUPATEN SERANG, PROVINSI BANTEN - -, Adi Hardiyono (Bulletin of Scientific Contribution, 2013)
The purpose study to recognize compatibility utilization igneous rock and volcanic breccia in research area based on rock characteristic and rock engineering properties. Igneous and volcanic breccias in the study area can be used as a basic building materials but need to be investigated compatibility use in accordance with the characteristics and properties owned engineering standards prevailing rock.